2021
DOI: 10.1007/jhep08(2021)036
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting dijet resonance searches for flavor physics

Abstract: In this work, we reinterpret ATLAS and CMS dijet resonance searches to set robust constraints on all hypothetical tree-level scalar and vector mediators with masses up to 5 TeV, assuming a diquark or a quark-antiquark coupling with an arbitrary flavor composition. To illustrate the application of these general results, we quantify the permissible size of new physics in $$ {\overline{B}}_q\to {D}_q^{\left(\ast \right)+}\left\{\pi, K\right\} $$ B … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 89 publications
(151 reference statements)
2
28
0
Order By: Relevance
“…A simple scaling was used in Ref. [74] to reinterpret the results [72,73] in the benchmark of new gauge boson W to other mediators. We have verified that the reinterpretation in Ref.…”
Section: Dijet Resonance Searchmentioning
confidence: 99%
“…A simple scaling was used in Ref. [74] to reinterpret the results [72,73] in the benchmark of new gauge boson W to other mediators. We have verified that the reinterpretation in Ref.…”
Section: Dijet Resonance Searchmentioning
confidence: 99%
“…In this paper, as an alternative, we shall examine possible NP interpretations of the deviations observed; for recent discussions along this line, see refs. [40][41][42][43][44][45].…”
Section: Jhep10(2021)235mentioning
confidence: 99%
“…As emphasized already in ref. [51], such an NLO analysis in the NP sector is crucial for reducing certain unphysical scale and renormalization scheme dependences present in the absence of these O(α s ) corrections [40][41][42][43][44][45]. It is numerically found that, under the combined constraints from the current experimental data, the deviations observed could be well explained at the 1σ level by the NP four-quark operators with γ µ (1 − γ 5 ) ⊗ γ µ (1 − γ 5 ) structure, and also at the 2σ level by the operators with (1 + γ 5 ) ⊗ (1 − γ 5 ) and (1 + γ 5 ) ⊗ (1 + γ 5 ) structures.…”
Section: Jhep10(2021)235mentioning
confidence: 99%
“…(s) → D + (s) π − [5][6][7][8]. Such decays are dominated by colour-allowed tree topologies JHEP10(2021)223…”
Section: Introductionmentioning
confidence: 99%